Sitting in and speaking out : student movements in the American South, 1960-1970 - Turner, Jeffrey A. (University of Georgia Press, 2010)
Jeffrey A. Turner argues that the story of student activism during the 1960s is too often focused on national groups like Students for a Democratic Society and events at schools like Columbia University and the University of California at Berkeley. Examining the activism of black and white students, he shows that the South responded to national developments but that the response had its own trajectory--one that was rooted in race. Turner looks at such events as the initial desegregation of campuses; integration's long aftermath as students learned to share institutions; the Black Power movement; and the antiwar movement.